The Impact of E-Commerce on the Growth of Micro, Small, and Medium Enterprises in Indonesia - Rolando, Benediktus (STKIP PGRI SITUBONDO, 2024)
This study examines the impact of e-commerce on the growth and development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through a systematic literature review analyzing 46 peer-reviewed references from the Scopus and Google Scholar database. The research employs qualitative synthesis to capture the nuanced experiences of MSME owners and stakeholders in their digital transformation journey. By systematically reviewing and synthesizing findings from prior research, the study provides a comprehensive understanding of how e-commerce adoption influences business performance, market expansion, and operational sustainability. The analysis reveals that e-commerce has significantly transformed MSMEs by enabling broader market reach, streamlining business processes, enhancing operational efficiency, and generating increased revenue streams. However, the study also identifies critical challenges impeding widespread digital adoption, including low digital literacy among entrepreneurs, inadequate technological infrastructure, limited access to digital financing, and complex regulatory frameworks. These barriers particularly affect MSMEs in rural and remote regions, creating a digital divide in Indonesia's MSME ecosystem. The findings contribute valuable insights for policymakers, business support organizations, and technology providers in developing targeted interventions to accelerate successful e-commerce adoption among Indonesian MSMEs.